Articulated Hip Distraction for Impingement of the Deformed Femoral Head in a Patient with Multiple Epiphyseal Dysplasia: A Case Report. Issue 3 (July 2018) - Jang, Woo Young; Cho, Tae-Joon
Abstract : Case: A 14-year-old boy with multiple epiphyseal dysplasia (MED) presented with right hip pain and stiffness. Radiographs revealed a deep notch at the superolateral part of the femoral head, which abutted the lateral corner of the acetabulum. Articulated hip distraction (AHD) was used to reduce the femoral head and obliterate the notch. At the 4-year follow-up, the radiographs showed a well-preserved joint space, and the patient had functional improvement. Conclusion: AHD may be an effective way to address and obliterate a superolateral femoral head notch and promote regeneration of the femoral head in a patient with MED.